A study on the redox, spectroscopic, and photophysical characteristics of a series of octahedral hexamolybdenum(ii) clusters: [Mo6X8Y6]2− (X, Y = Cl, Br, or I). Issue 4 (22nd December 2017) - Akagi, Soichiro; Fujii, Sho; Kitamura, Noboru
Abstract : We report a systematic study on the redox, spectroscopic, and photophysical properties of a series of [Mo6 X8 Y6 ] 2− (X, Y = Cl, Br, or I). Abstract : We report a systematic study on the redox, spectroscopic, and photophysical properties of a series of [Mo6 X8 Y6 ] 2− (X, Y = Cl, Br, or I.1–9 ). All of the [Mo6 X8 Y6 ] 2− clusters show intense and long-lived phosphorescence in both CH3 CN and crystalline phases at 298 K. We found that the emission quantum yields ( Φ em ) of1–9 increase in the sequences X = Cl < Br < I and Y = I < Br < Cl for given Y and X, respectively. The emission lifetimes ( τ em ) of the clusters also increase in the sequence Y = I < Br < Cl for given Mo6 X8 4+ -core clusters. The present data demonstrate that arbitrary combinations of X and Y in [Mo6 X8 Y6 ] 2− could tune τ em and Φ em in the ranges of 85–300 μs and 0.09–0.47, respectively. Both capping (X) and terminal ligand (Y) effects on the photophysical properties of the clusters are discussed on the basis of the energy gap ( i.e., emission energy) dependence of the nonradiative decay rate constant.